Structural And Electronic Properties of PtSe2/GaP Heterostructure. (2022) - Parmar, P.R.; Khengar, S.J.; Thakor, P.B.
Abstract: In this study, by employing the first principle calculations we have theoretically investigated the structural, electronic and optical properties of a two dimensional (2D) PtSe2 /GaP heterostructure. The optimized PtSe2 /GaP heterostructure has a hexagonal structure with a lattice constant of 3.83 Å. The band structure of PtSe2 /GaP heterostructure was obtained by applying the generalized gradient approximation (GGA) which shows the semiconducting nature. The investigation of optical properties suggests that the heterostructure PtSe2 /GaP shows absorption in the visible and ultraviolet region of the electromagnetic spectrum. It can be seen that PtSe2 /GaP heterostructure can be utilized in nanoelectronics and optoelectronic devices and its applications.